Enseñanza de la física por medio de la construcción de prototipos (2015)
The strategy for prototype construction and project-based learning have been applied for two semesters, in several electricity and magnetism courses, with engineering students of Escuela Colombiana de Ingeniería in 2014. This strategy is focused on three topics, namely: Electroscope (project1 P1), Torsion Balance (P2), and Van Graaff Generator (P3). Students build low-cost prototypes that allow them to integrate physical modelling, error analysis, and graphical analysis. This strategy allows improving the learning of electrostatics as well as other know-hows such as graphical expression and oral and written skills.